(3OjhGf GHf bdGbSs - (3GHf bdGbS , fUQ Hf YHO Gddg Hf YHO Gdbhj GddNejGdGYR, CHh GdaJhM,J (B567 (3g` s ((3jhSa Hf Ydj Hf eMeO GdedGM s)
(3ChdgG (B:s
(3bGd GdTjN GdCYR CHhGdaJhM jeOM CMO eTGQaj Ydi bGajI GdgeRI ce ebdI ddTbjb GdZV QeOGA EfSGfgG SGHM aj OeY CfOGA s
(3BNQgG (B:s
(3EPG GdhGOj LQi UHHG hbQJ Hg Yjfj adG SGd GdbQoqj hQH ZO hjhe djS jQVi Ydi MGd jSjQ Hg YToqj s
(3fSNI ofbdJ ef fSNI ocJHJ SjfI (B635(3g```s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B344s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B182 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B767s
Keywords: (3GdCOHs